THE ROLE OF INTERACTIVE METHODS IN IMPROVING TEACHING EFFECTIVENESS - Alijonov Komiljon,; Nematova Dilshoda,; Murodullayeva Zarina, (Ustozlar uchun, 2025)
Interactive methods play a crucial role in enhancing the effectiveness of teaching and reinforcing students' knowledge. This article explores the importance of interactive teaching methods in improving teaching outcomes, their impact on students, and how they can be effectively implemented in the classroom. Engaging students, involving them in the learning process, and applying what they have learned are essential aspects of interactive teaching.